Analysis of a grading system to assess the quality of small-bowel preparation for capsule endoscopy: in search of the Holy Grail - Goyal, Jatinder; Goel, Anshum; McGwin, Gerald; Weber, Frederick (Endoscopy International Open, 2014)
Background: The diagnostic yield of capsule endoscopy is vulnerable to inadequate visualization related to residual bile or chyme remaining in the lumen despite intestinal lavage. It has been challenging to determine the optimal lavage preparation of the bowel and patient diet before capsule endoscopy, as well as the timing of the procedure, because no well-accepted, validated grading system for assessing the quality of intestinal lavage before capsule endoscopy is available. There remains no consensus on the reliability of qualitative, quantitative, or computer-derived assessments of the quality of preparation for capsule endoscopy. This study evaluates intra-observer and interobserver agreement for a previously validated scale. Materials and methods: The digital images of 34 patients who underwent capsule endoscopy were independently reviewed by two blinded physicians according to a previously validated grading scale. One of the physicians reviewed and graded the patients a second time. The quality of the bowel luminal preparation was assessed with a qualitative parameter (fluid transparency) and a more quantitative parameter (mucosal invisibility) for each of three small-intestinal segments, and an overall small-bowel score for each parameter was assigned as well. A weighted kappa coefficient was used to calculate intra-observer (observer 1A and 1B) and interobserver (observer 1A and observer 2) agreement. A kappa value of 0.60 or more suggests strong agreement, 0.40 to 0.60 moderate agreement, and less than 0.40 poor agreement.Results: The intra-observer weighted kappa index for both fluid transparency and mucosal visibility was 0.52, which is consistent with moderate agreement. The interobserver weighted kappa indices for fluid transparency and mucosal invisibility were 0.29 and 0.42, respectively, demonstrating suboptimal interobserver agreement. The individual segment interobserver kappa indices were better for mucosal visibility (0.52, 0.39, and 0.47 for small-bowel segments 1, 2, and 3, respectively) than for fluid transparency (0.18, 0.38, and 0.31).Conclusions: The proposed grading scale for assessing the quality of preparation for capsule endoscopy has inadequate interobserver and intra-observer agreement. Capsule endoscopy preparation grading scales that focus more on quantitative than on qualitative assessment may demonstrate more reliable performance characteristics. Optimizing the quality of preparation and diagnostic yield of capsule endoscopy will first require the development of a well-validated grading scale.